A comparison of test manoeuvres for determining rearward amplification of articulated heavy vehicles. (1st September 2020) - Ni, Zhituo; Zhu, Shenjin; He, Yuping
Rearward amplification (RA) is an effective indicator of lateral stability for multi-trailer articulated heavy vehicles (MTAHVs). The International Organization for Standardization released the test manoeuvres, ISO-14791, for determining the indicator for MTAHVs. ISO-14791 recommends three methods, including two time-domain and one frequency-domain, to derive the RA measures. It was reported that the results from the three methods were not in good agreement. To explore this inconsistency among these methods, a multiple cycle sine-wave steering input (MCSSI) manoeuvre was simulated to obtain steady-state responses of MTAHVs. Furthermore, an automated frequency response method (AFRM) was used to derive the measures in the frequency-domain. This paper presents simulation results based on an A-Train Double. Results demonstrate that the steady-state RA measures under a MCSSI manoeuvre are in excellent agreement with those from frequency-domain methods. It is revealed that driver's steering behaviours impose a non-negligible impact on the transient RA measures of MTAHVs.